2015
DOI: 10.4103/2230-8210.149324
|View full text |Cite
|
Sign up to set email alerts
|

Addressing challenges and needs in patient education targeting hardly reached patients with chronic diseases

Abstract: Some patients do not benefit from participation in patient education due to reasons related to disease burden, literacy, and socioeconomic challenges. In this communication, we address more specifically both the challenges that these hardly reached patients face in relation to patient education programs and the challenges educators face when conducting patient education with hardly reached patients. We define principles for the format and content of dialogue tools to better support this patient group within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…The first contact with a HCP provides an opportunity for the PAH patient to talk and ask questions, whilst allowing the HCP to gain an understanding of the patient's needs in terms of education and information. Too much information can often be overwhelming [5] and patients may vary in the degree to which they benefit from participation in patient education due to disease burden, literacy levels and socioeconomic factors [32]. HCPs must gauge what level of information is appropriate and how much information the patient is able to process and retain at different stages of their disease.…”
Section: Role Of Hcpsmentioning
confidence: 99%
“…The first contact with a HCP provides an opportunity for the PAH patient to talk and ask questions, whilst allowing the HCP to gain an understanding of the patient's needs in terms of education and information. Too much information can often be overwhelming [5] and patients may vary in the degree to which they benefit from participation in patient education due to disease burden, literacy levels and socioeconomic factors [32]. HCPs must gauge what level of information is appropriate and how much information the patient is able to process and retain at different stages of their disease.…”
Section: Role Of Hcpsmentioning
confidence: 99%
“…It is also well known that practically all methods used in diabetes management and prevention are less effective in individuals who have access to fewer resources [33]. In other words, there is a need to direct our attention towards those who are most vulnerable and to try to understand how they can be motivated and involved as effectively as other groups.…”
Section: Equity In Health: Not Everyone Has the Same Opportunities Fomentioning
confidence: 99%
“…The approach addresses the challenges that these hardly reached patients face in relation to general patient education programmes and the challenges educators face when conducting patient education with hardly reached patients. In a qualitative study we identified four main categories of preferences for patient education that reaches out to these groups of patients: (1) flexibility related to start time, duration, and intensity; (2) simple and concrete education tools, with regard to design and extent; (3) being together, related to meeting people in a similar situation; and (4) respectful educators, related to constructive patient-educator relationships [33,34].…”
Section: Selected Projects Prominently Guided By the Principle Of Equmentioning
confidence: 99%
“…HEPs have been used to provide individuals with information concerning mental health, social health, physical health as well as emotional health 7–9. The other notable benefits that are associated with HEPs include the prevention of diseases and the reduction of the level of engagement of individuals in highly risky behaviours 10 11. When there are well-implemented HEPs, there can be various positive changes in behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…When there are well-implemented HEPs, there can be various positive changes in behaviour. This has been shown to have the ability to significantly lower the risks that are associated with alcohol, tobacco as well as other types of drugs 6–11…”
Section: Introductionmentioning
confidence: 99%